Pengembangan Aplikasi Manajemen Informasi Sedekah Berbagi Makanan Berbasis Android Dengan Metode Rekayasa Perangkat Lunak Berorientasi Penggunaan Ulang - Annisa Fitriani Nur; Agi Putra Kharisma; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Giving alms is one of the activities that is highly recommended in Islam. Giving alms could be done by giving money, goods, and food. One of the obstacles almsgiving is there's no adequate information about the detail of event will be held, such as time and place of the event. Therefore, these problem can be solved by an alms information management aplication. This application requires a maps viewer to show information about the location of the event, nearby location searching, and other components reuse. This application is using a software engineering method based on components reuse with component retrieval in its development. Method of components reuse consists of requirements analysis, components analysis, requirements modification, design with reuse, construction, and testing. This application is using UML (Unified Modeling Language) modeling language and Java programming language with Android SDK (Software Development Kit) in implementation. This application has been tested through the unit testing, integration testing, and validation testing. Unit testing and integration testing are using white-box approach then validation testing is using black-box approach.